The Role and Molecular Mechanism of Action of Surfactant Protein D in Innate Host Defense Against Influenza A Virus - Hsieh, I-Ni; De Luna, Xavier; White, Mitchell R.; Hartshorn, Kevan L. (Frontiers in Immunology, 2018)
Influenza A viruses (IAVs) are a major ongoing public health problem due continuous mutation of viral surface proteins. Cell binding by IAV and the initial steps of the viral life cycle in the cell are determined by the viral hemagglutinin (HA) which attaches to specific sialic acid conjugates on the surface of respiratory epithelial or immune cells. IAV is a prime example of the importance of innate immunity in early host protection against infection. Our research has focused on the role of soluble lectin inhibitors in lung fluids that provide an initial barrier to IAV infection and also modulate host inflammatory responses to the virus. In general these inhibitors act by binding to the viral HA to limit infection. Surfactant protein D (SP-D) attaches to mannosylated glycans on the HA in a calcium dependent manner. In contrast, surfactant protein A and ficolins present sialic acid rich ligands to which the HA can bind. SP-D appears to play a particularly important role in defense against seasonal IAV strains. In contrast, pandemic IAV strains are not inhibited by human SP-D due to relative lack of glycosylation of the IAV head or cell binding portion of their HA. In addition, avian strains of IAV generally have limited HA glycosylation and are not inhibited by SP-D. In collaborative studies our laboratory has generated mutant versions of SP-D with increased affinity for mannose rich glycans and these mutants have increased ability to neutralize seasonal IAV, as well as being able to inhibit pandemic IAV in vitro and in vivo. Through crystallography, molecular modeling, and molecular dynamics we have determined the molecular mechanism of binding of SP-D to the IAV HA and established the basis for increased inhibitory activity of mutant versions of SP-D.